Coincidence and Common Fixed Points For Hybrid Mappings Satisfying an Implicit Relation and Applications: Valeriu Popa, Alina-Mihaela Patriciu - Team, Support (Thai Journal of Mathematics, 2017)
In this paper a fixed point theorem for a pair of hybrid mappings involving altering distance and satisfying an implicit relation is proved, generalizing the main result from [26] (Theorem3.1).